Acurácia de medidas lineares dos seios maxilar e frontal na estimativa do sexo de indivíduos do nordeste brasileiro: um estudo com tomografias computadorizadas multislice - Mendonça, Diego Santiago de (2020)
The human identification process represents one of the most relevant aspects of the forensic sciences field. Few studies related to sex dimorphism have evaluated the accuracy of linear measurements of frontal and maxillary sinuses on multislice computed tomographies (MCT). This investigation aimed to: (1) evaluate parameters of accuracy in sex estimation of maxillary and frontal sinuses on MCT of Brazilian adult individuals; (2) develop and cross-validate a new formula for discriminating males and females. Two-phase cross-sectional research was conducted with a statistically estimated sample of 140 MCTs: phase 1) development of a formula based on both sinuses (50 males and 50 females); phase 2) validation study (20 males and 20 females). Frontal and maxillary sinuses linear measurements (height, width, and diameter) were assessed using the RadiAnt DICOM software. Based on a multivariate statistical approach, a new formula combining both paranasal sinuses was developed and further validated. Receiver operating characteristic (ROC) curves, the area under the curve (AUC), sensitivity, specificity, positive and negative predictive values, accuracy, and likelihood ratio were obtained. Also, the influence of age was evaluated by subgroup statistical analysis. Men showed higher mean values of width, height, and diameter of the studied paranasal sinuses (p<0.05). The maxillary sinuses were a better predictor of sex estimation than frontal sinus (accuracy between 61-74% and 58-69%, respectively). The highest accuracy was found with the distance between the right and left maxillary sinuses (74%).The formula for sex estimation showed a sensitivity of 80%, specificity of 95.5%, and an accuracy of 87.5%. In individuals aged > 30 years, there was a 63.1% reduction in predictive values for sex estimation. Frontal and maxillary sinuses measurements were adequate predictors for sexual dimorphism in a Brazilian sample. Both paranasal sinuses showed a better estimation of males, and the most significant accuracy occurred with maxillary sinuses. High precision was found with the distance between the right and left maxillary sinuses. The multivariate statistics-based formula provided a better precision in discriminating males and females.